2011
DOI: 10.1175/2010waf2222420.1
|View full text |Cite
|
Sign up to set email alerts
|

Some Implications of Core Regime Wind Structures in Western North Pacific Tropical Cyclones

Abstract: In this study, a tropical cyclone (TC) is considered to be compact if 1) the radius of maximum wind or the maximum tangential wind is smaller than what would be expected for an average tropical cyclone of the same intensity or the same radius of maximum wind, and 2) the decrease of tangential wind outside the radius of maximum wind is greater than that of an average TC. A structure parameter S is defined to provide a quantitative measure of the compactness of tropical cyclones. Quick Scatterometer (QuikSCAT) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…The decreasing trend of IR with the increase in AR34 for AR34 larger than 150 km suggests that smaller outercore size or compact structure favors RI, as also shown in Chen et al (2011). Note that for a given intensity and RMW, a larger AR34 indicates a slow decaying rate for the tangential wind with radius outside the RMW.…”
Section: B Dependence On Storm Sizementioning
confidence: 56%
See 1 more Smart Citation
“…The decreasing trend of IR with the increase in AR34 for AR34 larger than 150 km suggests that smaller outercore size or compact structure favors RI, as also shown in Chen et al (2011). Note that for a given intensity and RMW, a larger AR34 indicates a slow decaying rate for the tangential wind with radius outside the RMW.…”
Section: B Dependence On Storm Sizementioning
confidence: 56%
“…Recent observational studies have begun to focus on the potential impact of TC structure on its intensification (Chen et al 2011;Rogers et al 2013;Carrasco et al 2014). Chen et al (2011) found that compact TCs (either small RMW, or weak outer-core wind, or both) had a higher IR and more frequent rapid intensification (RI) relative to incompact storms over the western North Pacific.…”
Section: Introductionmentioning
confidence: 99%
“…5). A value of during-TC SST near 30°C under intense TC-ocean interaction is one of the highest reported over STY Megi (Lin et al 2013;D'Asaro et al 2014 showing small-RMW TCs are more likely to undergo RI (Emanuel 1989, Chen et al 2011, Carrasco et al 2014, Xu and Wang 2018. As RI began, both STYs had a substantial contraction of their RMW, but Hagibis's RMW contracted more rapidly than Haiyan (~30 km to ~10 km in 6 h vs.18 h, respectively) during P1.…”
Section: (A) Ri Period (P1)mentioning
confidence: 86%
“…Previous studies confirmed that TC landfall impacts (e.g. rainfall and wind) are affected by TC characteristics including track direction (Lee et al, 2006;Chan et al, 2019), intensity (Emanuel, 2005;Yu et al, 2017), size (Matyas, 2006;Chen et al, 2011), translation speed (Su et al, 2012;Hsu et al, 2013), duration (Done et al, 2018), asymmetric structure (Lonfat et al, 2004;Chen et al, 2016), as well as interactions among these characteristics (Teng et al, 2020a). Landfall impacts are also affected by the interaction of TCs with the land surface, causing phase-locked wind and rainfall patterns (Chang et al, 1993;Lin et al, 2001;Chiao and Lin, 2003;Hsu et al, 2013;Lu et al, 2018).…”
Section: Introductionmentioning
confidence: 87%